Emergency abdominal surgery in patients with left ventricular assist device: short- and long-term results - Gündeş, Ebubekir; Uzun, Orhan; Çiyiltepe, Hüseyin; Aday, Ulaş; Çetin, Durmuş Ali; Gülmez, Selçuk; Senger, Aziz; Kirali, Kaan (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2017)
Introduction : Emergency abdominal surgery (EAS) in patients with long-term mechanical circulatory support and strong anticoagulation is very difficult. Aim : To present our experiences regarding the short- and long-term results of patients with a left ventricular assist device (LVAD) who underwent emergency abdominal surgery under general anesthesia at a large tertiary healthcare center. Material and methods : The electronic medical records of 7 patients with LVAD who underwent EAS between January 1, 2010 and December 31, 2016 were retrospectively investigated in order to evaluate perioperative management and outcomes. The patients were divided into two groups based on the need for EAS procedures. Results : Seven (9.2%) of 76 patients with LVAD underwent EAS an average of 79.1 ±79.4 days after implantation. No statistically significant differences were found between the groups with and without EAS with regard to demographic characteristics, type of device, and rate of perioperative mortality (p > 0.05). The indications for surgery, retroperitoneal hematoma in 2 patients and in 5 other patients; ileus, iatrogenic splenic injury associated with thoracentesis, splenic abscess, acute abdominal pain and rectal cancer surgery was a pelvic abscess in a patient who is connected to the stump. In all cases laparotomy was performed with median incision. The perioperative mortality rate was 28.6% (n = 2). Two patients underwent orthotopic heart transplant during long-term follow-up. Conclusions : The EAS is not rare during LVAD treatment but is a rather complex procedure. General surgeons will be increasingly likely to encounter such patients as their numbers rise and their life expectancies are prolonged.